Peaceful Democratic Transition in Pakistan & Mediated Effects of Panama Leaks Case: A Philosophical Review - Seemab Far Bukhari (Journal of Peace, Development and Communication, 2022)
Active participation of people and their understanding of the system are the philosophical roots of democracy. In this context, mass media of any society work as the backbone to form the public opinion through its contents. On April 20, 2017 through a landmark decision, the Supreme Court of Pakistan disqualified incumbent Prime Minister of Pakistan Nawaz Sharif from holding his public office for life on the Panama Leaks Case. However, the historic decision was proven another example of disqualification of incumbent Prime Ministers of Pakistan. Under the theoretical perspective of cultivation, this study tends to investigate effects of Pakistan`s electronic media coverage of Panama Leaks Case on the perceptions of Pakistani youth and how this coverage affected their opinion about peaceful democratic transition.